2016
DOI: 10.1186/s11671-016-1403-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of zinc hydroxystannate-decorated graphene oxide nanohybrids and their synergistic reinforcement on reducing fire hazards of flexible poly (vinyl chloride)

Abstract: A novel flame retardant, zinc hydroxystannate-decorated graphene oxide (ZHS/GO) nanohybrid, was successfully prepared and well characterized. Herein, the ZHS nanoparticles could not only enhance the flame retardancy of GO with the synergistic flame-retardant effect of ZHS but also prevent the restack of GO to improve the mechanical properties of poly (vinyl chloride) (PVC) matrix. The structure characterization showed ZHS nanoparticles were bonded onto the surface of GO nanosheets and the ZHS nanoparticles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 32 publications
(26 reference statements)
1
28
0
Order By: Relevance
“…Metals or metal derivative-based nanomaterials include metal oxides, metal hydroxides and other metallic compounds, such as Co 3 O 4 [106], SnO 2 [107], Ce-MnO 2 [108], TiO 2 [109,110], CuO [111], NiO [106], [114], NiCe x O y [115], ZrO 2 [116], Ni(OH) 2 [116], MnCo 2 O 4 [38], FeOOH [117], AlOOH [118], NiAl-LDH [119] (LDH represents to layered double hydroxide), NiFe-LDH [120], Co(OH) 2 [121], ZnS [122], ZnCO 3 [123], MoS 2 [124], Al(H 2 PO 2 ) 3 [125], ferrocene (Fc) [126], zirconium organophosphate [127], nano-Sb 2 O 3 [128] and zinc hydroxystannate [129,130]. They can also be classified into zero-dimensional nanoparticles, onedimensional nanowires/nanorods/nanotubes and two-dimensional nanoplates/nanobelts.…”
Section: Inorganic-nanomaterials Graphene-based Composite Flame Retarmentioning
confidence: 99%
“…Metals or metal derivative-based nanomaterials include metal oxides, metal hydroxides and other metallic compounds, such as Co 3 O 4 [106], SnO 2 [107], Ce-MnO 2 [108], TiO 2 [109,110], CuO [111], NiO [106], [114], NiCe x O y [115], ZrO 2 [116], Ni(OH) 2 [116], MnCo 2 O 4 [38], FeOOH [117], AlOOH [118], NiAl-LDH [119] (LDH represents to layered double hydroxide), NiFe-LDH [120], Co(OH) 2 [121], ZnS [122], ZnCO 3 [123], MoS 2 [124], Al(H 2 PO 2 ) 3 [125], ferrocene (Fc) [126], zirconium organophosphate [127], nano-Sb 2 O 3 [128] and zinc hydroxystannate [129,130]. They can also be classified into zero-dimensional nanoparticles, onedimensional nanowires/nanorods/nanotubes and two-dimensional nanoplates/nanobelts.…”
Section: Inorganic-nanomaterials Graphene-based Composite Flame Retarmentioning
confidence: 99%
“…Meanwhile, the limit oxygen index (LOI) value was increased by 1.5%. The flame retardancy of GO/PVC composites has been improved to a certain extent . Jiang et al found that the PHRR and THR of EP with 2 wt% GNS were decreased by 30.9% and 17.0%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of these applications demand flexibility and are therefore well served by the unique attributes of flexible PVC (fPVC). However, the flammable nature of fPVC restricts its application in certain areas; large amounts of heat and toxic smoke are released by the combustion of PVC which, in certain circumstances, could lead to heavy casualties and property losses in the event of a fire . Reducing the fire hazard presented by fPVC is, therefore, a subject of great concern.…”
Section: Introductionmentioning
confidence: 99%